The abhidhamma philosophy, or, The psycho-ethical philosophy of early Buddhism - Kāśyapa, Jagadīśa, Bhikkhu (Bharatiya Vidya Prakashan, 1982)
On abhidharmma philosophy of the Theravada school in Buddhism.